Comorbidities, risk factors and outcomes in patients with heart failure and an ejection fraction of more than or equal to 40% in primary care- and hospital care-based outpatient clinics. (3rd April 2018) - Eriksson, B.; Wändell, P.; Dahlström, U.; Näsman, P.; Lund, L. H.; Edner, M.
Abstract: Objective: The aim of this study is to describe patients with heart failure and an ejection fraction (EF) of more than or equal to 40%, managed in both Primary- and Hospital based outpatient clinics separately with their prognosis, comorbidities and risk factors. Further to compare the heart failure medication in the two groups. Design: We used the prospective Swedish Heart Failure Registry to include 9654 out-patients who had HF and EF ≥40%, 1802 patients were registered in primary care and 7852 in hospital care. Descriptive statistical tests were used to analyze base line characteristics in the two groups and multivariate logistic regression analysis to assess mortality rate in the groups separately. Setting: The prospective Swedish Heart Failure Registry. Subjects: Patients with heart failure and an ejection fraction (EF) of more than or equal to 40%. Main outcome measures: Comorbidities, risk factors and mortality. Results: Mean-age was 77.5 (primary care) and 70.3 years (hospital care) p  < 0.0001, 46.7 vs. 36.3% women respectively ( p  < 0.0001) and EF ≥50% 26.1 vs. 13.4% ( p  < 0.0001). Co-morbidities were common in both groups (97.2% vs. 92.3%), the primary care group having more atrial fibrillation, hypertension, ischemic heart disease and COPD. According to the multivariate logistic regression analysis smoking, COPD and diabetes were the most important independent risk factors in the primary care group and valvular disease in the hospital care group. All-cause mortality during mean follow-up of almost 4 years was 31.5% in primary care and 27.8% in hospital care. One year-mortality rates were 7.8%, and 7.0% respectively. Conclusion: Any co-morbidity was noted in 97% of the HF-patients with an EF of more than or equal to 40% managed at primary care based out-patient clinics and these patients had partly other independent risk factors than those patients managed in hospital care based outpatients clinics. Our results indicate that more attention should be payed to manage COPD in the primary care group. KEY POINTS: 97% of heart failure patients with an ejection fraction of more than or equal to 40% managed at primary care based out-patient clinics had any comorbidity. Patients in primary care had partly other independent risk factors than those in hospital care. All-cause mortality during mean follow-up of almost 4 years was higher in primary care compared to hospital care. In matched HF-patients RAS-antagonists, beta-blockers as well as the combination of the two drugs were more seldom prescribed when managed in primary care compared with hospital care.